Fluoro-substituted conjugated polyindole for desirable electrochemical charge storage materials. (10th October 2019) - Wang, Rui; Lin, Kaiwen; Jiang, Fengxing; Zhou, Weiqiang; Wang, Zhenfeng; Wu, Yanli; Ding, Yongbo; Hou, Jian; Nie, Guangming; Xu, Jingkun; Duan, Xuemin
Abstract: Fluoropolymers have great values in the scientific research and the industrial application, but poor electrochemical properties restricted their use as charge storage materials. In this work, we developed a high-performance poly(5-fluoroindole) (5-PFIn) as charge storage material by simple electrodeposition of 5-fluoroindole in acetonitrile solution containing 0.1 M Bu4 NBF4 . The morphologies, structures and electrochemical properties of as-prepared 5-PFIn were studied by SEM, FT-IR, UV–vis, BET and electrochemical techniques, respectively. The electrochemical results indicated that the 5-PFIn nanowires in 1.0 M H2 SO4 electrolyte showed a full-covered strongly responsive redox behavior between −0.4 V and 0.85 V, which remarkably differed from polyindole (PIn) and poly(5-methoxyindole) (5-PMeOIn) and poly(indole-5-carboxylic acid) (5-PICA). As a result, 5-PFIn exhibited high specific capacitance of 416 F g −1 at 10 A g −1, good cycling stability of 83% after 5000 cycles and slow self-discharge behavior, which were superior to those of PIn (103 F g −1, 68%), 5-PMeOIn (114 F g −1, 70%) and 5-PICA (286 F g −1, 70%). These results indicated that the fluorine-substituted conjugated PIn will be one of the most promising fluoropolymers electrode materials for supercapacitor application.